How Does the Spatial Misallocation of Land Resources Affect Urban Industrial Transformation and Upgrading? Evidence from China - Shangui Peng; Jian Wang; Hao Sun; Zhengning Guo (Land, 2022)
Industrial transformation and upgrading is a key variable for developing countries to become developed countries. In China’s institutional environment, the central government’s decisions regarding the spatial allocation of land resources cause a differentiation in the evolution of industrial structures and formats among regions, generating significant impacts on urban industrial transformation and upgrading (UITU), with important policy implications. Using panel data from 276 prefecture-level cities in China from 2007 to 2019, this study constructs a spatial panel econometric model and a mediating effect model to reveal how land spatial misallocation (LSM) affects UITU. The results show that, LSM is not conducive to UITU, and this adverse effect is greater in cities with a relative land supply shortage than in cities with a relative land supply surplus. Further research finds that the LSM caused by the relative land supply shortage affects the UITU mainly through intermediate mechanisms that crowd out the investments and financing for real industries and inhibit residents’ demand and innovation, and the LSM caused by the relative land supply surplus affects the UITU mainly through intermediate mechanisms that enhance the survival of low-end industries and disrupt the institutional environment. From these findings, this study not only puts forward specific policy recommendations for optimizing the allocation of land resources in China to promote UITU, but also discusses the implications for related research and practice in other countries.